Management of acute self-limited pain in patients in a health center - Batista, Sílvia (2008)
Introduction: The treatment of pain is a capacity shared by the physician and the patients.Well-informed self-medication is beneficial for the population and for the Health System; however, frequent mistakes add to the risk of adverse effects. Goals: To depict the self-limited episodes of acute pain and the respective therapeutic management featured in the examined sampling. To study the self-medication cases in terms of frequency and connection with socio-demographic factors. Methods: The cross-sectional study was based on a sampling of 352 patients from the Cacém Health Care Centre (Olival extension), using one questionnaire for each of the personal interviews concerning self-limited acute pain and its therapeutic management during the 30 preceding days. Results: There were 89 episodes of self-limited acute pain (25.3%), mainly women. The most frequent episodes consisted of headaches (48.3%),myalgia and flu syndrome-related headaches (10.1%) and rachialgia (7.9%). Of the 89 patients that referred an episode of self-limited acute pain in the 30 days prior to the questionnaire, 63.0% relied solely on pharmacotherapy, while 12.4% resorted to non-pharmacological therapeutic as well. The most widely used drugs were Paracatemol (50.7%) and NSAIDs (31.3%). Self-medication was frequent (46.5%), mostly on women of less than 45 years of age; it was associated with sub-therapeutic drugs and was based on prior medical indication or self-decision. Discussion: It was observed that there are significant associations between self-medication and a few socio-demographic factors and that self-medication hinders an adequate posology.The importance of self-decision in the context of self-medication was also noted; the study suggests that the patients must be better clarified about the properties of the drugs.